Risk Attitudes of Nascent Entrepreneurs: New Evidence from an Experimentally Validated Survey - Marco Caliendo; Frank M. Fossen; Alexander S. Kritikos (European University Viadrina, Department of Business Administration and Economics, 2006)
The in°uence of risk aversion on the decision to become self-employed is a much discussed topic in the entrepreneurial literature. Conventional wisdom asserts that being an entrepreneur means making risky decisions in uncertain environments; hence more risk-averse individuals are less likely to become entrepreneurs. Empirical tests of this assumption are scarce, however, mainly because reliable measures of risk aversion are not available. We base our analysis on the most recent waves of the German Socio-Economic Panel (SOEP), which allow us to use experimentally validated measures of risk attitudes. Most importantly and in contrast to previous research, we are able to examine whether the decision of starting a business is in°uenced by objectively measurable risk attitudes at the time when this decision is made. Our results show that in general, individuals with lower risk aversion are more likely to become self-employed. Sensitivity analysis reveals, however, that this is true only for people coming out of regular employment, whereas for individuals coming out of unemployment or inactivity, risk attitudes do not seem to play a role in the decision process.
Keywords: J23; D81; M13; 330; Risk Attitudes; Entrepreneurship; Self-Employment